2012
DOI: 10.1074/mcp.m111.014720
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferricin B Inhibits the Phosphorylation of the Two-Component System Response Regulators BasR and CreB

Abstract: Natural antimicrobial peptides provide fundamental protection for multicellular organisms from microbes, such as Lactoferricin B (Lfcin B). Many studies have shown that Lfcin B penetrates the cell membrane and has intracellular activities. To elucidate the intracellular behavior of Lfcin B, we first used Escherichia coli K12 proteome chips to identify the intracellular targets of Lfcin B. The results showed that Lfcin B binds to two response regulators, BasR and CreB, of the two-component system. For further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…Furthermore, bLfcin inhibits phosphorylation of the response regulators and of the two-component system's (TCSs) cognate sensor kinases. The role of the TCS is to protect the integrity of bacterial cell membranes against antimicrobial peptides [76]. However, the homologous examination of response regulators and sensor kinases in probiotics, including Bifidobacterium and Lactobacillus, showed that this motif was not present, suggesting that bLfcin may have only marginal effects on the microbioma probiotics in the intestine [76].…”
Section: In Vitro Antibacterial and Anti-fungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bLfcin inhibits phosphorylation of the response regulators and of the two-component system's (TCSs) cognate sensor kinases. The role of the TCS is to protect the integrity of bacterial cell membranes against antimicrobial peptides [76]. However, the homologous examination of response regulators and sensor kinases in probiotics, including Bifidobacterium and Lactobacillus, showed that this motif was not present, suggesting that bLfcin may have only marginal effects on the microbioma probiotics in the intestine [76].…”
Section: In Vitro Antibacterial and Anti-fungal Activitymentioning
confidence: 99%
“…The role of the TCS is to protect the integrity of bacterial cell membranes against antimicrobial peptides [76]. However, the homologous examination of response regulators and sensor kinases in probiotics, including Bifidobacterium and Lactobacillus, showed that this motif was not present, suggesting that bLfcin may have only marginal effects on the microbioma probiotics in the intestine [76]. In addition to antimicrobial properties, Lfcin of human and bovine origin has also been found to be effective in inhibiting the classical complement pathway.…”
Section: In Vitro Antibacterial and Anti-fungal Activitymentioning
confidence: 99%
“…Lactoferricin B was the first AMP shown to interfere with phosphorylation of the two-component system to suppress bacterial growth (91). It inhibits phosphorylation of the two response regulators by their cognate sensor kinases BasS and CreC.…”
Section: Protein Biosynthesis and Metabolism Inhibitorsmentioning
confidence: 99%
“…The proteome array that contains 铣90% of the proteins encoded by the E. coli K12 genome has been constructed. It has been used to investigate DNA damage (19), identify serological biomarkers of inflammatory bowel disease (20), and reveal the inhibition mechanism of lactoferricin B (21). The proteome chip is a good tool to comprehensively screen for bacterial proteins potentially able to interact with fimS or its adjacent regions.…”
Section: Discussionmentioning
confidence: 99%
“…As for bacterial proteome chips, we have previously constructed the E. coli K12 proteome array that contains the proteins encoded in 4256 of the 4288 genes in the E. coli K12 genome (19). This array has been used for investigating DNA damage (19), identifying serological biomarkers of inflammatory bowel disease (20), and revealing the inhibition mechanism of lactoferricin B (21). In the present study, we used the E. coli K12 proteome chip to screen for novel E. coli proteins that can interact with the promotercontaining fimS.…”
mentioning
confidence: 99%